Аналіз дзета-потенціалу при попередній поверхневій обробці картону для одноразового посуду - Роїк, Т. А.; Бичкар, Є. С. (ТОВ «Видавництво Ліра-К», 2025)
The article presents changes in the zeta potential of the cardboard surface as a result of the cardboard surface’s pretreatment with AluPAC coagulant, which affects the hydrophilic properties of the cardboard during the subsequent application of a polyethylene coating. The research results allow us to recommend the use of aluminium hydroxychloride coagulant AluPAC in the production of preliminary surface treatment of cardboard.
Keywords: обробка картону; картон